The Ideal Punishment for Corporations that False the Brand of the Theory of Dignified Justice - Rizky Karo Karo; Debora Pasaribu; Irene Puteri A.S Sinaga; Arnoldus Pawe (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The corporation is an organized collection of persons and/or wealth, whether it is a legal entity or non-legal entity [Article 1 point 1 of Supreme Court Regulation No. 13 of 2016). Corporations are established to seek profit / profit unlawfully. Marks are one of the intellectual property rights protected by Law No. 20 of 2016 concerning Marks and Geographical Indications (Law 20/2016). Trademark rights holders are protected by Law 20/2016 from counterfeiting acts. This paper will discuss penalties both regulated in Law 20/2016 or will be regulated in Law Number 1 of 2023 concerning the Criminal Code [KUHP (Law 1/2023)] concerning corporate punishment. The formulation of the problem raised is how is the ideal punishment for corporations that falsify the perspective brand of dignified justice theory? The research method used is the normative juridical method. The author uses secondary data in the form of primary legal material, secondary legal material, and tertiary. And the author uses qualitative analysis to come up with a conclusion. The result of the study, namely the theory of dignified justice, is a theory initiated by Teguh Prasetyo, Professor of the Faculty of Law, Universitas Pelita Harapan, this theory is based on Pancasila and aims to humanize humans (nge wong ke wong-in Javanese). The Criminal Code (Law 1/2023) provides guidance on the requirements for corporations that can be criminally liable. Based on the Criminal Code (Law 1/2023), the criminal for corporations is the main crime in the form of fines, and additional crimes. Meanwhile, based on Law 20/2016, imprisonment and/or fines may be  imposed, for example: sentenced to a maximum of 5 (five) years imprisonment and/or a maximum fine of  Rp2,000,000,000.00 (two billion rupiah). The ideal crime & in accordance with the theory of dignified justice for the corporation is the criminal fine, and destruction of goods from the counterfeited brand, as well as the revocation of licenses.